Stochastic Non-Excitable Systems with Time Delay Modulation of Noise Effects by Time-Delayed Feedback - Geffert, Paul M (Springer, 2015)
Stochastic effects in nonlinear dynamical systems are an important field of state of-the-art research. The interplay of noise, nonlinearity, and time-delayed feedback leads to a wealth of novel, unexpected phenomena, such as stochastic bifurcations, coherence resonance, etc. Stochastic bifurcation denotes the transition from a monomodal to a bimodal stationary probability distribution, and coherence res onance is a counterintuitive effect which describes the nonmonotonic dependence of the coherence of noise-induced oscillations upon noise strength, resulting in an optimum coherence at non-zero noise strength...